State of the Art and Perspectives of Wave Energy in the Mediterranean Sea: Backstage of ISWEC - Mattiazzo, Giuliana (Frontiers in Energy Research, 2019)
According to the European Commission, sea waves have a great potential as renewable energy source. Despite wave energy technology is a field in continuous development, it is not yet competitive with the other renewables, due to the small quantities of devices sold, most of them being prototypal solutions at level. So far, various Wave Energy Converter concepts have been developed and some of them tested in full scale. The most recurrent test environment is the North Atlantic Ocean, which possesses high energy potential. The Mediterranean Sea on the other hand is less energetic, but also possesses less dangerous extreme conditions. It represents a favorable starting point to develop technologies that later will be scaled up to more powerful sites. This article illustrates the wave energy potential of the Mediterranean and analyses the wave energy converters engineered according to sea states characteristic of the Mediterranean Sea. Focus is brought to the Inertial Sea Wave Energy Converter (ISWEC) technology, which is one of the few Mediterranean concept to have reached Technology Readiness Level (TRL) 7. The article will document the deployment and the following open sea test campaign of a full-scale prototype off the shore of Pantelleria Island, Italy.